ANALISIS PENERAPAN MEKANISME PENOMORAN FAKTUR PAJAK SEBAGAI UPAYA PENINGKATAN PENERIMAAN PAJAK PERTAMBAHAN NILAI (Studi Pada Kantor Pelayanan Pajak Madya Malang) - Prasetyo, Andie (Jurnal Mahasiswa Perpajakan, 2014)
Value Added Tax (VAT) is one kind of tax that becoming main tax for Government. There many kind of case that becoming obstacle to gain VAT Revenue. Most of the cases is using the operandi modus for fictitious tax invoice. As preventive action, Direktorat Jenderal Pajak (DJP) issued new regulations PER-24/PJ/2012. If the Taxpayer had a full right for numbering their tax invoices, then DJP would have a full right to give a number for VAT Invoices. The result of this study showed that the application of numbering tax invoices mechanism in Tax Office Madya Malang is properly correct with the regulation. There are significant result that the amount of National Fictitious Tax invoices and the amount of loss because Fictitious Tax invoices is decrease. Meanwhile, There's still happened Fictitious Tax invoices so that make loss in term of gaining VAT revenue, even tough there's still happened on that case. Fortunately, the amount of Taxpayer who is indicated use Multiple Tax Invoices is decrease . The loss is decrease which is caused tax invoices that multiple indicated make the revenue of VAT Revenue in Tax Office Madya Malang is increase. The target achievement rate of VAT revenues is fluctuated. The contribution is increase after Tax Office used numbering mechanism. Keywords : Numbering Mechanism, Fictitious Tax Invoices, Multiple Tax Invoices, Value Added Tax